2015
DOI: 10.2500/ajra.2015.29.4172
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Predicts Chronic Rhinosinusitis without Nasal Polyps: A Population-Based Study

Abstract: COPD was associated with an increased risk of CRSsNP in this study population, independent of a number of potential confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…CRS was identified in this study by the claims records showing a primary diagnosis of CRS designated with the use of the International Classification of Diseases, Ninth Revision (ICD-9) codes CRS1517 (ICD-9 codes: 473, 473.0, 473.1, 473.2, 473.3, 473.8, and 473.9) from 1996 to 2007. Date of diagnosis was set as the index date.…”
Section: Methodsmentioning
confidence: 99%
“…CRS was identified in this study by the claims records showing a primary diagnosis of CRS designated with the use of the International Classification of Diseases, Ninth Revision (ICD-9) codes CRS1517 (ICD-9 codes: 473, 473.0, 473.1, 473.2, 473.3, 473.8, and 473.9) from 1996 to 2007. Date of diagnosis was set as the index date.…”
Section: Methodsmentioning
confidence: 99%
“…13,17 A Taiwan population-based study also demonstrated that chronic obstructive pulmonary disease (COPD) is independently associated with CRSsNP. 18 …”
Section: Phenotypes and Endotypesmentioning
confidence: 99%
“…Cases and controls were followed for both CRSwNP and CRSsNP as outcomes. Following previous studies, ICD‐9‐CM codes for CRS were 473, 473.0, 473.1, 473.2, 473.3, 473.8, and 473.9. Those for CRSwNP and CRSsNP were 471, 471.0, 471.1, 471.8, and 471.9.…”
Section: Methodsmentioning
confidence: 99%